Mobbing – Moral Harassment at Work as a triggering factor for Work Stress in Nurses - Saraiva Mendes, Bruna Miriam (2024)
Introduction: The experience of Moral Harassment at Work (MHW) in Nursing has important consequences, which accentuate the relevance of research in the area. Objective/s: Characterize the studies that assume the status of sample elements. Identify categories that express the contours of the MHW; to analyze the rationale of the literature for the categories of MHW found. Methods: Systematic review of the literature, based on the sample, selected in Web of Science and PubMed databases, using the PRISMA method and PICO criteria. The selection emerges from the search expression and MeSH terms, conjugated with the Boolean operators (Moral Harassment) OR (Mobbing) OR (Bullying) AND (Nursing) AND (Workplace) AND (Stress). A total of 261 studies were eligible for review, of which 11 answered the research question; emerging from 4 countries in Europe, 4 in Asia, 1 in South America and 1 in Australia. Results: Eighteen categories were identified that express the contours of MHW: the strong categories are "Burnout – emotional exhaustion and depersonalization", based on 8 Discursive Components (DC), from 6 studies, followed by "Job dissatisfaction, Feelings of failure and Frustration" from 5 CDs from 5 studies; and also "Occupational Stress, Lower Stress Management Capacity", "Relationship Between Exposure to Vertical/Horizontal Bullying and Job Satisfaction" by 4 CDs of 4 studies, respectively. Conclusion: The comorbidities resulting from MHW - burnout and psychosomatic symptomatology - are indicators for further investigation and training of nurses, as well as for the implementation of preventive strategies.